Reduction of skull size in South American sea lions reveals density-dependent growth during population recovery - Drago, M. (2010)
Craniometrical data of male and female skulls collected from 1974 to 2007 were used to test the hypothesis that the somatic growth of South American sea lions Otaria flavescens in northern Patagonia has been affected by a reduction in the per capita food availability, due to a combination of the population recovery after cessation of sealing and the development of industrial fishing targeting Argentine hake Merluccius hubbsi. Most of the 19 craniometric variables considered decreased through time in both sexes, and the same trend was found for a variable extracted by means of principal component analysis that was related to skull volume. Most of the reductions in skull size and volume have happened since 1990, when the sea lion population peaked and the hake population collapsed. This evidence, combined with a review of supplementary data derived from stable isotope analysis, supports the hypotheses that the somatic growth of South American sea lions is densitydependent and that industrial fishing has reduced the carrying capacity of the ecosystem for South American sea lions.